Computational design of ancestral and consensus sequence of apical membrane antigen 1 (AMA1) of Plasmodium spp - Rizky Nurdiansyah; Rahmat Azhari Kemal (Indonesian Society for Biochemistry and Molecular Biology, 2019)
Background: It is important to design a malaria vaccine targeting all human malaria parasites as well as non-human primate parasites to eradicate malaria and prevent zoonotic malaria. Apical membrane antigen 1 (AMA1) protein is shared by human-infecting Plasmodium species. Ancestral sequence reconstruction (ASR) and consensus sequence construction on AMA1 might be able to overcome the antigenic distinction between those species. Objective: We aimed to computationally design the ancestral and consensus sequence of Plasmodium AMA1 protein and analyze the sequences for its putative immunogenicity. Methods: We utilized bioinformatics software to computationally design ancestral and consensus sequences of AMA1 protein. AMA1 protein sequences of human-infecting Plasmodium and non-human primate Plasmodium were retrieved from PlasmoDB. ASR was designed using MEGA X while consensus was inferred using UGENE. Phylogenetic tree consisting of existing Plasmodium sequences and the ancestral sequence was constructed using IQTREE webserver and visualized with FigTree. Results: Phylogenetic analysis showed that Plasmodium spp. were divided into 2 major groups, P. falciparum (Clade F) and non-falciparum (Clade NF) thus three ancestral and consensus sequences were designed based on each clade and both clades at once. Reconstructed ancestral sequences were located as sister branch for naturally occurring strains. On the contrary, consensus sequences are located within the branch of corresponding naturally occurring strains. Sequence analysis showed the presence of CD8+ T cell epitope in all computationally-designed sequences. Conclusion: Ancestral and consensus AMA1 sequences are potential for further studies as a malaria vaccine candidate.